John Dewey - Narayan, John (Manchester University Press, 2016)
"This book argues that John Dewey should be read as a philosopher of globalization rather than as a 'local' American philosopher. Although Dewey's political philosophy was rooted in late nineteenth and early twentieth century America, it was more importantly about the role of America in a globalized world. In returning to, and recovering the neglected global dimensions of Dewey's political philosophy, the book highlights how his insights about globalization and democracy can inform present theoretical debates. John Narayan traces the emergence of Dewey as a global democrat through an examination of his work from The public and its problems (1927) onwards. Narayan shows how Dewey sets out an evolutionary form of global and national democracy in his work, that has not been fully appreciated even by contemporary scholars of pragmatism, and which offers valuable lessons for the twenty-first century and for our own hopes for global democracy."